Emerging technologies for maintenance management of residential and commercial high-rise buildings: barriers and strategies for improvement - Mohd Sakhaf, Muhammad Wafiq; Ayob, Mohd Fairullazi (IIUM Press, 2024)
The rapid development in the innovation of technologies facilitates the facilities management (FM) industry in terms of efficiency and sustainability. In recent years, the adoption of emerging technologies has been attracting a lot of interest among stakeholders. This is because Malaysia is in the process of transforming towards smart facilities management (Smart FM) from traditional facilities management (TFM). Therefore, this paper prepared to present the outcome of the study on the types of emerging technologies used, drivers, barriers and strategies towards the adoption of smart FM of residential and commercial high-rise buildings in Klang Valley. A semi-structured interview with facilities management (FM) professionals was conducted to identify the types of emerging technologies used in the Malaysian FM industry, drivers, barriers as well as strategies for adopting the advanced technologies for maintenance management of high-rise buildings. From the study, the FM professionals validated that Building Information Modelling (BIM) is the most effective and efficient technology to be used in the maintenance management of residential and commercial high-rise buildings. The emerging technologies help to increase building efficiency and are suitable for long-term investment planning. However, high adoption costs and the limited number of experts on the technologies in Malaysia are the major barriers. Despite the barrier, the significant strategy was found to be effective in improving the adoption through training and workshops. Thus, this paper provides a comprehensive understanding of emerging technologies and marks a turning point for an organisation to consider adoption.